Sosiaalipolitiikan lumo - Halmetoja, Antti; Koistinen, Pertti; Ojala, Satu (Tampere University Press, 2016)
Social and the ecological welfare should be taken as the main aim of all politics. This is the message of this book titled The Enchantment of Social Policy. Basic social security system needs to be rebuilt and grounded on the universal basic income that everyone can top up by participating to the society in different ways. Universal basic income can be seen as a mean to recognize all valuable participation to for example voluntary work or care of elderly people. In conditions of high unemployment, this kind of universalistic social security would weaken the nexus between employment and welfare. It would promote a society and culture that is less dependent on the exploitation of natural resources. This book describes building blocks that are needed to reconstitute the enchantment of social policy - the utopian that we should collectively pursue.